Economic Growth, Money Supply, Government Spending, Government Revenue and Inflation in Nigeria: An Empirical Perspective - Harper, Alan; Sokunle, Raufu; Rachevski, Israel (Archives of Business Research, 2024)
This study examines the relationship between real GDP (RGDP) and key economic variables—money supply, inflation, government spending, government revenue, and exchange rates—in Nigeria from 2004 to 2019. Using a multiple regression model, the findings reveal a strong fit, with an R Square value of 0.723, indicating that 72.3% of the variability in RGDP is explained by the model. The results show that government spending and revenue have a significant positive impact on economic growth, while inflation and money supply are associated with negative effects. The exchange rate also positively influences RGDP, though to a lesser extent. These findings highlight the importance of prudent fiscal and monetary policies in fostering sustained economic growth in Nigeria.